The Christian Spirituality of Cardinal Sou-hwan Kim: Contextualized and Interpreted - Pak, Pyong-Gwan (Journal of Korean religions, 2015)
The late Cardinal Sou-hwan Kim (Kim Suhwan) is well known for his role in the democratization process and his defense of human rights in South Korea over almost two decades (1970s–1980s). Nevertheless, very little is known about the prelate’s inner, religious world, which inspired his prophetic voice that had a crucial impact on both the ecclesiastical and the civic life of the country. This study aims at investigating his spirituality, that is, the totality of his religious thoughts, ideals, values, ethos, motivations and intentions, which animated his concern for and involvement in the socio-political realities of South Korea of his day. For an in-depth understanding, it attempts to contextualize and interpret Kim’s Christian spirituality. Therefore, focusing on his biographical and historical context, it highlights details that have significant bearing on his life, experience, and spirituality. Furthermore, by theological contextualization, it brings out the fundamental theological orientations and characteristics of Kim’s spirituality. It demonstrates that his spirituality exemplified a novel theological-spiritual development that has emerged in worldwide contemporary Catholicism. Kim’s spirituality, it argues, emerged in his earnest effort to live as faithfully as possible a life of Christian faith, with the new vista and understanding opened up by Vatican Council II and post-conciliar liberation theology. It also examines the more personal, intimate dimensions of Kim’s spirituality, and offers an interpretative consideration of its salient features.